X-RAY OPTICS : Method for formation of quasi-monochromatic divergent X-ray fluxes from laser-produced plasmas. (28th September 2016) - Shevelko, A P
Abstract: Conditions and applicability limits of a new method for formation of quasi-monochromatic, with a large solid angle of divergence, linear X-ray fluxes from laser-produced plasmas are considered. The method is based on a special combination of laser target elements and K-absorption filters, when the spectra of [H]- and [He]-like ions are excited in laser-produced plasma and K-absorption filters select only the resonance lines of these ions from the linear spectrum. Experimental and theoretical studies have shown that, in the fluxes formed, the degree of monochromatisation λ/Δλ may reach ∼100 at the radiation contrast ratio of 5 – 10 and angular divergence of ∼π sr.